A Brain-Based Instruction Simulation Approach to Improve Code Team Response in an Internal Medicine Unit. (October 2018) - Clapper, Timothy C.; Rajwani, Kapil; Mauer, Elizabeth; Gerber, Linda M.; Lee, Joanna; Ching, Kevin; Miller, Stephanie; Gudi, Kirana
Background and Objectives. The code team course is a 3-hour, interactive course that follows a4-phase brain-based lesson plan for simulation .Interprofessional teams receive instruction and practice in evidence-basedteamwork, communication, and individual skills. Methods. This quantitative research included a pre-test and post-test design in an urban Department of Medicine. Sixteen groups (n=109) participated in the course over a period of eight weeks. Classroom metrics included pre- and post-courseHigh-Quality cardiopulmonary resuscitation (CPR) and code team didactic knowledge assessed by Wilcoxon rank-sum tests. In addition, fourin-situ mock code simulations were conducted to provide the researchers with baseline and post-intervention data.Code team performance assessment scores were tallied and compared between baseline and post-intervention by Fisher's Exact Test. Results. The classroom metrics produced significant results.High-Quality CPR scores were higher post-training than pre-training (median score 4 vs. 3, respectively; p=0.006). Didactic knowledge test scores were also significantly higher (median score 90 vs. 70, respectively; p <0.001).In-situ team performance improved in several areas. There was a significant improvement in the area ofcardiac code management in the day shift group. The percent "done well" improved from 25% (5/20) to 100% (20/20) (p= <0.001). Conclusion. The results of this pilot study suggest that code team training using the4-phase BBL plan for simulation is associated with improvements ininterprofessional team knowledge and performance duringcardiac emergencies . It is equally important that the training is conducted over a short period in order to ensure that all team members are properly prepared.